2016
DOI: 10.1136/emermed-2015-205581
|View full text |Cite
|
Sign up to set email alerts
|

Are there too few women presenting at emergency medicine conferences?

Abstract: Introduction There is a perception that women are under-represented as speakers at emergency medicine (EM) conferences. We aimed to evaluate the ratio of male to female speakers and the proportion of presenting time by gender at major international EM conferences. Methods Conference programmes of the major English-speaking EM conferences occurring from 2014 to 2015 were obtained. The number of presentations, the gender of the speaker and the duration of each presentation were recorded. Results We analysed eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 6 publications
5
39
0
Order By: Relevance
“…A first step is to provide job‐specific mentorship to senior residents with individualized attention and coaching on CV building, interviewing techniques, and contract negotiation. In addition, improvements in the hiring process such as gender‐blind evaluations and incorporating women in recruitment as well as acknowledging the existing biases could help . Educational interventions targeting gender bias in hiring practices have demonstrated enhanced awareness after program implementation.…”
Section: Strategies Across the Career Continuum: Priming The Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…A first step is to provide job‐specific mentorship to senior residents with individualized attention and coaching on CV building, interviewing techniques, and contract negotiation. In addition, improvements in the hiring process such as gender‐blind evaluations and incorporating women in recruitment as well as acknowledging the existing biases could help . Educational interventions targeting gender bias in hiring practices have demonstrated enhanced awareness after program implementation.…”
Section: Strategies Across the Career Continuum: Priming The Pipelinementioning
confidence: 99%
“…As described above, women are less likely to be promoted to associate and full professors and have leadership positions than men . Gender imbalances in many areas pertinent to promotions, such as authorship, grant funding, speakerships, and participation on editorial boards, have been well documented and need to be addressed …”
Section: Retention Strategiesmentioning
confidence: 99%
“…The excellent thought-provoking article by Sunga and Kass in the EMJ has outlined an intervention aimed at developing the speaking skills of women in EM 1. In their paper, they state that the evidence suggests that only 29.9% speakers at international EM conferences were women 2. It was this along with their own observations of how few women were keynote speakers that gave the idea for this study.…”
mentioning
confidence: 91%
“…2 In contrast, an analysis of programs from eight international emergency medicine conferences from 2014 to 2015 found that only 29.9% of presentations were given by women. 3 However, the proportion of qualified female emergency medicine specialists in the United States, Canada, United Kingdom, and Australia ranged from 23.5 to 30.0%, suggesting that no relative discrepancy exists. Supporting these findings, a recent large analysis of 181 medical and surgical conferences in the US and Canada found that over the last decade (2007-2017) the mean proportion of female speakers (34.1%) was similar to the mean proportion of active female physicians across all specialties (32.4%) during the same time period.…”
Section: Introductionmentioning
confidence: 99%